Study on textural changes and pectin degradation of tarocco blood Orange during storage. Issue 1 (31st December 2022) - Frempong, Kwame Eduam Baiden; Chen, Yan; Wang, Zhenxing; Xu, Jianxiong; Xu, Xinrui; Cui, Wenting; Gong, Hongying; Peng, Dongsheng; Liang, Lili; Meng, Yushan; Lin, Xiaoyan
ABSTRACT: Pectin degradation in the cell walls and middle lamella greatly affects the texture and the quality of the fruit including the taste and storage time. This directly affects its acceptability, supply to the consumer market, and economic benefits. It is therefore essential to establish the relationship between the chemical changes of pectin and the texture of the fruit to improve its preservation. This study was designed to evaluate the degradation of pectin in the peels of Tarocco blood orange and the textural changes during postharvest storage and further investigate their relationship over the study period. The texture of the fruit was characterized using the texture profile analyzer and the degradation of pectin was investigated by testing the content of the pectin, degree of esterification, and galacturonic acid content. The physicochemical properties, such as weight loss, moisture content, and anthocyanin content were also measured. Furthermore, the structural changes of the pectin were analyzed by molecular weight determination and FTIR test. The results showed that the Mw of pectin decreased from 568.05 kDa to 362.55 kDa, with a 42.1% decline in pectin content for storing for 63 d. The gradual solubilization, depolymerization, and de-esterification of the pectin consequently led to the decline in the textual properties of the fruit during postharvest storage. This can be applied and lead to improvements in quality control and process design in the food industry and the marketplace for the fruit during storage and preservation.